Taxation and systematic risk under decreasing returns to scale - Diderik Lund (Copenhagen Business School (CBS), Department of Economics, 2006)
Lund (2002a) showed in a CAPM-type model how tax depreciation schedules affect required expected returns after taxes. Even without leverage higher tax rates implied lower betas when tax deductions were risk free. Here they are risky, and marginal investment is taxed together with inframarginal in an analytical model of decreasing returns. With imperfect loss offset tax claims are analogous to call options. The beta of equity is still decreasing in the tax rate, but increasing in the underlying volatility. The results are important if market data are used to infer required expected returns, and in discussions of tax design.
hdl:10398/7643
Keywords: F23; G31; H25; 330; Corporate tax; depreciation; imperfect loss offset; decreasing returns; cost of capital; uncertainty